Drinking guidelines for exercise: What evidence is there that athletes should drink "as much as tolerable", "to replace the weight lost during exercise" or "ad libitum"? - Noakes, T. D. (Journal of Sports Sciences, 2007)
The most recent (1996) drinking guidelines of the American College of Sports Medicine (ACSM) propose that athletes should drink "as much as tolerable" during exercise. Since some individuals can tolerate rates of free water ingestion that exceed their rates of free water loss during exercise, this advice has caused some to overdrink leading to water retention, weight gain and, in a few, death from exercise-associated hyponatraemic encephalopathy. The new drinking guidelines of the International Olympic Committee (IOC), recently re-published in this Journal, continue to argue that athletes must drink enough to replace all their weight lost during exercise and to ingest sodium chloride since sodium is "the electrolyte most critical to performance and health". In this rebuttal to that Consensus Document, I argue that these new guidelines, like their predecessors, lack an adequate, scientifically proven evidence base. Nor have they been properly evaluated in appropriately controlled, randomized, prospective clinical trials. In particular, these new guidelines provide erroneous recommendations on five topics.